2011
DOI: 10.1137/100816663
|View full text |Cite
|
Sign up to set email alerts
|

Fourth Order Time-Stepping for Kadomtsev–Petviashvili and Davey–Stewartson Equations

Abstract: Abstract. Purely dispersive partial differential equations as the Korteweg-de Vries equation, the nonlinear Schrödinger equation and higher dimensional generalizations thereof can have solutions which develop a zone of rapid modulated oscillations in the region where the corresponding dispersionless equations have shocks or blow-up. To numerically study such phenomena, fourth order time-stepping in combination with spectral methods is beneficial to resolve the steep gradients in the oscillatory region. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(174 citation statements)
references
References 39 publications
3
171
0
Order By: Relevance
“…The approach is then applied to the D-bar problem of the Davey-Stewartson (DS) II equation, and the resulting solution is compared to a direct numerical solution of DS II as in [13].…”
Section: (6)mentioning
confidence: 99%
See 1 more Smart Citation
“…The approach is then applied to the D-bar problem of the Davey-Stewartson (DS) II equation, and the resulting solution is compared to a direct numerical solution of DS II as in [13].…”
Section: (6)mentioning
confidence: 99%
“…In [13] it was shown that the error in the numerical conservation of the DS II energy tends to overestimate the numerical accuracy of the solution in an L ∞ sense by two to three orders of magnitude.…”
Section: Time Dependence Of Ds II Solutionsmentioning
confidence: 99%
“…For equations of the form (23) with diagonal L, there are many efficient high-order time integrators, see e.g. [30,23,33,35] and references therein. This allows for an efficient integration in time.…”
Section: Numerical Study Of Weakly Dispersive Regularizations Of Burgmentioning
confidence: 99%
“…Accuracy of the numerical solution is controlled as discussed in [33,35,34] via the numerically computed energies (10) and (14) which will depend on time due to unavoidable numerical errors. We use the quantity…”
Section: Numerical Study Of Weakly Dispersive Regularizations Of Burgmentioning
confidence: 99%
“…The step size is chosen adaptively using the socalled H211b digital filter [56,57] to meet the prescribed error tolerance, set as of the order of machine precision. A more detailed study of time-discretization accuracy for similar spectral models can be found in [38].…”
Section: Symbolic Codingmentioning
confidence: 99%